Students’ Learning Strategies to Acquire Vocabulary Using TikTok by 8th Grade of SMPN 1 Mataram - Andriana, Devina Rizki Ayu; Muhaimi, Lalu; Lail, Husnul (Program Studi Pendidikan Bahasa Inggris, 2024)
This study aims to identify the learning strategies used by students in acquiring vocabulary through TikTok, the hurdles that they face, and how they overcome them utilizing the Oxford’s (1990) theory. This study is designed to use a qualitative descriptive method. The majority of the data in this study are collected through focus group discussions (FGDs), questionnaires, interviews, and documentation. The subjects of this study consist 66 of eighth-grade students at SMPN 1 Mataram who use TikTok for vocabulary acquisition. The analysis reveals that the overall use of learning strategies in acquiring vocabulary through TikTok is at a medium level, with an average score of 2.73. The most frequently used strategy is the affective strategy, with an average score of 3.06. Meanwhile the least utilized strategy is the social strategy, with an average score of 2.04. Other strategies include memory (3.05), cognitive (2.87), compensation (2.87), and metacognitive strategies (2.52). Furthermore, the findings indicate that the most common hurdles faced by students include difficulties in understanding vocabulary, reported by 30% of the students, followed by a lack of detailed explanations (20%), variability in content quality (18%), and inaccurate subtitles (14%). Students primarily overcome these hurdles by using additional tools (27%), followed by asking experts (18%), repeating videos (15%), and seeking other videos (11%). The implications of these findings suggest that enhancing students’ awareness of effective learning strategies and improving content quality could significantly benefit vocabulary acquisition through digital platforms.